Anisotropic Rock Model-Guided Post-Stack Attribute Analysis With Pore Type and Production Data for a Carbonate Gas Reservoir - Huang, Xuri; Xu, Yungui; Li, Haoyuan; Zhang, Zhiwen; Xu, Wei (Frontiers in Earth Science, 2021)
The Moxi (MX) area is dominated by carbonate gas reservoirs. The pore type is the major factor for its gas productivity. Its favorable reservoirs are mainly affected by three types of pore structures. Among them, the fractured-cave type is the most favorable pore structure. Cave and vuggy types are the second most favorable. The inter-particle pore type is the least. It is important to distinguish the three pore types spatially for a cost-effective development. However, due to a lack of wide azimuthal seismic data, it is difficult to identify the pore types. It would be practical to identify the seismic signature in post-stack data of the pore type and its related productivity. In this work, a theoretical model of Hudson's anisotropic representation is constructed. Seismic forward modeling is conducted based on the theoretical model. The pre-stack and post-stack signatures of the anisotropy in pore types are analyzed. The rock model is further calibrated with logs. Forward modeling is performed based on the calibrated logs. The signatures in the post-stack data are analyzed, then a new attribute is proposed for these signatures. The attribute is applied to the 3D seismic data. By correlating the pore types with this attribute, it turns out that the attribute can differentiate the pore types compared to other conventional attributes. Furthermore, the attribute is correlated with the open flow gas rate of the wells. It has a quite reasonable correlation. This further proves that the attribute from post-stack data could be a good indicator for the pore types and gas productivity. Also, the attribute can be easily mapped spatially such that the new drilling locations can be selected.